CHAYOTE (SECHIUM EDULE JACQ. SWARTZ) EXTRACT AND FRACTIONS IMPROVE MDA LEVELS AND TESTOSTERONE HORMONES IN MALE RATS WITH TYPE 2 DIABETES - Imelda Montes Monika Simanungkalit; Jekson Martiar Siahaan; Hendrika Silitonga (RADJA PUBLIKA, 2024)
This study aimed to analyze the effects of chayote (Sechium edule Jacq. Swartz) extract and fractions on male reproductive function, specifically by observing Malondialdehyde (MDA) levels and testosterone hormones, in a rat model of type 2 diabetes. The study used a laboratory experimental method with a posttest-only controlled group design on male Wistar rats. The rats were randomized into 17 groups, including a negative control group, a positive control group, and groups that received ethanol extract, n-hexane fraction, ethyl acetate, and water of chayote at doses of 50 mg/KgBW, 100 mg/KgBW, and 150 mg/KgBW. The results showed that the ethanol extract, n-hexane fraction, and ethyl acetate of chayote can reduce MDA activity and increase testosterone hormone levels in male white rats (Rattus novergicus) induced by streptozotocin, NA, and HFD. This study suggests that chayote has the potential to be used as a natural ingredient to improve male reproductive function in people with type 2 diabetes.